전신 부종과 동반되어 급격하게 진행한 증식당뇨망막병증 1예 - 임준현(Jun Hyun Lim); 이승욱(Seung Uk Lee); 이상준(Sang Joon Lee); 남기엽(Ki Yup Nam) (Daihan angwa haghoi jabji, 2017)
목적: 비증식당뇨망막병증으로 경과 관찰 중 전신 부종 발생 후 황반부종 및 급격한 증식당뇨망막병증 진행이 발생한 증례를 경험하여 이를 보고하고자 한다. 증례요약: 1주 전부터 시작된 양안 시력 저하를 주소로 48세 남자가 내원하였다. 5개월 전 중등도 비증식당뇨망막병증 진단 후 경과관찰 중이었으며 내원 3주 전까지 큰 변화는 없었다. 내원 당일 시행한 검사에서 양안 황반부종 및 신생혈관이 관찰되었다. 시력저하와 함께 심한 전신 부종이 발생하였다고 하였다. 전형적인 당뇨황반부종 양상은 아니라고 판단하여 유리체강 내 항혈관내피형성인자주사는 보류하고 신장내과에 진료 의뢰하였다. 심부전 및 당뇨병콩팥병증 악화로 판단되어 열흘간 이뇨제 복용 및 저염식이 치료 후 내원하였으며 시력 호전 및 황반부종 소실이 확인되었다. 이후 증식당뇨망막병증에 대한 치료로 유리체강 내 항혈관내피형성인자주사 및 범망막광응고술을 시행 받았으나 결국 우안 유리체출혈이 발생하여 수술을 시행하였다. 결론: 전신 부종을 동반한 갑작스런 황반부종 및 증식당뇨망막병증 진행이 발생한 증례를 경험하여 보고하는 바이며 당뇨망막병증경과 관찰 시 급격한 진행과 관련된 인자로서 전신부종에 대한 고려도 필요할 것으로 사료된다. Purpose: We report a case of rapid progression to proliferative diabetic after generalized edema occurrence in a non proliferative diabetic retinopathy patient. Case summary: A 48-year-old man visited our hospital with both eyes visual disturbance which occurred 1 week ago. He was diagnosed with moderate non proliferative diabetic retinopathy 5 months ago and there was no significant interval change 3 weeks ago. Date of visit, diffuse macular edema and neovascularization were observed in both eyes. Accompanying visual disturbance, he had generalized edema and 10 kg of weight gain. We thought it was not common diabetic macular edema, we held ophthalmic treatment such as an intravitreal anti-vascular endothelial growth factor (anti-VEGF) injection and requested medical treatment to the department of nephrology. Diagnosed with aggravation of left ventricle heart failure and diabetic nephropathy, he took diuretics and low salt diet for 10 days. After 10 days, his visual acuity improved and macular edema disappeared. Since then, he received intravitreal anti-VEGF injection and panretinal photocoagulation for proliferative diabetic retinopathy treatment. Nevertheless, he underwent pars plana vitrectomy due to vitreous hemorrhage in right eye. Conclusions: We experienced a case of sudden diffuse macular edema and progression to proliferative diabetic retinopathy associated with generalized edema. We suggest that it is necessary to consider systemic changes in diabetic retinopathy. KCI Citation Count: 0